2016
DOI: 10.1086/688900
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Significance of Pulmonary Arterial Capacitance in Pulmonary Arterial Hypertension: Single‐Center Experience

Abstract: This study explores the prognostic utility of pulmonary arterial capacitance (PAC) in a diverse cohort of patients with pulmonary arterial hypertension (PAH) from a tertiary referral center and compares it with the prognostic utility of other hemodynamic parameters. PAC is a strong independent predictor of mortality in patients with PAH.Keywords: pulmonary arterial hypertension, pulmonary arterial capacitance, prognosis.Pulm Circ 2016;6(4):608-610. DOI: 10.1086/688900.The importance of pulmonary arterial capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 10 publications
1
14
0
Order By: Relevance
“…PAC has been studied and shown reasonable prognostication ability. [19][20][21] A prior study showed an AUC of 0.61 for discrimination of 1 year mortality; discriminatory ability was similar for PAC, mRAP, mean pulmonary arterial pressure, cardiac index, and PVR. 21 Cardiac index and stroke volume have been acknowledged to be strong predictors of prognosis but were not significant for prediction of mortality in our study (Table 2).…”
Section: Discussionmentioning
confidence: 89%
“…PAC has been studied and shown reasonable prognostication ability. [19][20][21] A prior study showed an AUC of 0.61 for discrimination of 1 year mortality; discriminatory ability was similar for PAC, mRAP, mean pulmonary arterial pressure, cardiac index, and PVR. 21 Cardiac index and stroke volume have been acknowledged to be strong predictors of prognosis but were not significant for prediction of mortality in our study (Table 2).…”
Section: Discussionmentioning
confidence: 89%
“…The most feasible option to obtain PAC is a ratio of stroke volume to pulmonary artery pulse pressure measured by RHC. Despite of the fact that this method overestimates real compliance, hence does not include amount of blood flow from the pulmonary circulation into the capillary bed during systole, it was proven as significant prognostic factor in PAH [ 23 ]. Interestingly, some studies confirmed that low PAC (and worse prognosis) was observed in PAH patients, even when PVR was normal.…”
Section: Discussionmentioning
confidence: 99%
“…Although PA compliance is a major determinant of RV work 14 and has great impact on prognosis in various cardiac diseases, 1 4 its estimation has remained challenging. Therefore, in the present study, we chose to assess PA compliance using the PPP.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional catheterization-based measures of PA compliance PA compliance has traditionally been calculated using two methods: designated systolic PA compliance (sPAC), which is determined from measures of pulse pressure and stroke volume indexed to BSA and expressed as stroke volume / Pmax -Pmin (mL/mmHg Á m 2 ), [1][2][3][4] where Pmax -Pmin is the difference between the minimum and maximum PAP; and diastolic PA compliance (dPAC), which is estimated based on a two-element Windkessel model that assumes that compliance and hemodynamic resistance are constant during the measurement. 6,7 PA compliance can also be estimated based on the PAP profile during diastole.…”
Section: Cardiac Catheterizationmentioning
confidence: 99%
See 1 more Smart Citation